Clinical Efficacy of Acupuncture in the Treatment of Uterine Contraction Pain Post-Cesarean Section: Protocol of a Randomized Controlled Trial - Deng Y; Li Z; Zhang T; Tang X; Luo Y; Li Q; Zhang S; Liu Z; Tang D; Ai Z; Guo T; Liang F (Journal of Pain Research, 2025)
Yuanzheng Deng,1,* Zhengping Li,2,* Tiankui Zhang,3,* Xin Tang,1 Yan Luo,4 Qifu Li,5 Shumin Zhang,1 Zili Liu,1 Diwei Tang,1 Zhenghai Ai,6 Taipin Guo,1 Fanrong Liang5 1School of Second Clinical Medicine/The Second Affiliated Hospital, Yunnan University of Chinese Medicine, Kunming, People’s Republic of China; 2Traditional Chinese Medicine Department of Preventive Care, Ludian County Hospital of Traditional Chinese Medicine, Zhaotong, People’s Republic of China; 3Department of Acupuncture and Moxibustion, Ludian County Hospital of Traditional Chinese Medicine, Zhaotong, People’s Republic of China; 4Department of Obstetrics, Ludian County Hospital of Traditional Chinese Medicine, Zhaotong, People’s Republic of China; 5College of Acupuncture and Tuina, Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of China; 6Department of Internal Medicine, Ludian County Hospital of Traditional Chinese Medicine, Zhaotong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Taipin Guo, School of Second Clinical Medicine/The Second Affiliated Hospital, Yunnan University of Chinese Medicine, Kunming, People’s Republic of China, Tel +86 18487272658, Email gtphncs@126.com Fanrong Liang, College of Acupuncture and Tuina, Chengdu University of Traditional Chinese Medicine, Chengdu, People’s Republic of China, Tel +86 13608058216, Email acuresearch@126.comPurpose: Uterine contraction pain post-cesarean section (UCPCS) is one of the main complaints for mothers in the early stages of the puerperium. Acupuncture, a non-pharmacological therapy, has shown sound analgesic effects with almost no toxic side effects. This study uses acupuncture as an intervention and aimed to provide strong evidence for the clinical efficacy of acupuncture in treating UCPCS.Patients and Methods: This single-blind, randomized controlled trial (RCT) was conducted at the Ludian County Hospital of Traditional Chinese Medicine, China. Participants (138) are randomly assigned in a 1:1 ratio to either an observation or control group following cesarean section. Both groups receive routine postpartum care, the control group with sham acupuncture and the observation group with conventional acupuncture for 3 days. The primary outcome is the mean Visual Analogue Scale (VAS) score of the UCPCS. Secondary outcomes include the mean of UCPCS intensity, frequency, total duration, number of days to disappear, amount of vaginal bleeding and lactation, time to first lactation, and the Edinburgh Postnatal Depression Scale (EPDS) score. The final results will be analyzed in accordance with the intention-to-treat (ITT) principle using SPSS V.28.0.Discussion: This is the first RCT using non-penetrating sham acupuncture as a control to validate the clinical efficacy of acupuncture for UCPCS. The results of this study are expected to provide an effective therapeutic option for UCPCS, as well as offer clinicians and researchers strong evidence regarding non-pharmacological interventions.Keywords: uterine contraction pain post-cesarean section, acupuncture, protocol, randomized controlled trial